Synthetic Biology-Based Approaches for Microalgal Bio-Removal of Heavy Metals From Wastewater Effluents - Sattayawat, Pachara; Yunus, Ian S.; Noirungsee, Nuttapol; Mukjang, Nilita; Pathom-Aree, Wasu; Pekkoh, Jeeraporn; Pumas, Chayakorn (Frontiers in Environmental Science, 2021)
Heavy metal polluted wastewater from industries is currently one of the major environmental concerns leading to insufficient supply of clean water. Several strategies have been implemented to overcome this challenge including the use of microalgae as heavy metal bio-removers. However, there are still limitations that prevent microalgae to function optimally. Synthetic biology is a new biological discipline developed to solve challenging problems via bioengineering approaches. To date, synthetic biology has no universally affirmed definitions; however, it is uncontroversial that synthetic biology utilizes a constructive library of genetic standardized parts to create new biological systems or to redesign existing ones with improved characteristics. In this mini-review, we present state-of-the-art synthetic biology-based approaches that can be used to enhance heavy metal bio-removal from wastewater effluents by microalgae with a narrative synthetic biology workflow (Design-Build-Test-Learn cycle) to guide future developments of more advanced systems. We also provide insights into potent genes/proteins responsible for the bio-removal processes for stepwise developments of more advanced systems. A total of 49 unique genes and proteins are listed based on their 8 heavy metals (Mn, Fe, Cu, Zn, As, Cd, Hg, and Pb) bio-removal functions in transport system, cellular tolerance, synthesis of key players in heavy metal bio-removal, biotransformation of heavy metals, and gene expression regulation. Thus, with our library, genetic parts are ready to be recruited for any synthetic biology-based designs. Thereby, this mini-review identifies potential avenues of future research and maps opportunities to unleash more potential of microalgae as heavy metal bio-removers with synthetic biology.